2005
DOI: 10.1080/00365510500375263
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage, DNA susceptibility to oxidation and glutathione level in women with polycystic ovary syndrome

Abstract: Recent studies have addressed the possibility of an association between polycystic ovaries and ovarian cancer. DNA damage is the first step of the carcinogenesis, and susceptibility to cancer, in general, is characterized by high DNA damage. Free radical-mediated DNA damage and impaired antioxidant defence have been implicated as contributory factors for the development of cancer. This study evaluates DNA damage (strand breakage, base oxidation, formamidopyrimidine DNA glycosylase (Fpg) sensitive sites), H2O2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 28 publications
7
53
0
2
Order By: Relevance
“…This study could be used as an evidence for confirmation of recent studies about the omega-3 effect on ovary tissue (16). Superoxide dismutase (SOD) produced in cumulus oophorus cells is closely associated with oocyte maturation and also GPx and catalase are significant for reproduction health; moreover, GSH as a redox system exists in a large amount in the oocytes ,so according to this study, it seems that omega-3 may modulate the ROS effect by affecting on these anti-oxidative systems but it is necessary more studies to confirm this idea (12,17,18). Superoxide (O2 -), hydrogen preoxide (H2O2), and lipid peroxides are generated in luteal tissue during natural and prostaglandin-induced regression in the rat.…”
Section: Discussionmentioning
confidence: 80%
“…This study could be used as an evidence for confirmation of recent studies about the omega-3 effect on ovary tissue (16). Superoxide dismutase (SOD) produced in cumulus oophorus cells is closely associated with oocyte maturation and also GPx and catalase are significant for reproduction health; moreover, GSH as a redox system exists in a large amount in the oocytes ,so according to this study, it seems that omega-3 may modulate the ROS effect by affecting on these anti-oxidative systems but it is necessary more studies to confirm this idea (12,17,18). Superoxide (O2 -), hydrogen preoxide (H2O2), and lipid peroxides are generated in luteal tissue during natural and prostaglandin-induced regression in the rat.…”
Section: Discussionmentioning
confidence: 80%
“…Oxidative stress is increased in diabetes and also in obesity [23,24] . Studies also demonstrated elevated oxidative stress in insulin-resistant women with PCOS [25][26][27] . Increased reactive oxygen species generation induced by hyperglycemia and/or hyperinsulinemia has been reported in this population [28,29] .…”
Section: Introductionmentioning
confidence: 98%
“…Increased reactive oxygen species generation induced by hyperglycemia and/or hyperinsulinemia has been reported in this population [28,29] . However, there were conflicting results about the levels of antioxidants in these studies [25][26][27] . Some investigators [26,27] found decreased levels of antioxidants, whereas others [25] have observed increased activities of some antioxidants as a compensatory mechanism in PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important cause of menstrual irregularities ranging from amenorrhea to menorrhagia, as well as androgen excess in women. PCOS is also considered to be an oxidative state, based on decreased antioxidant concentrations, reduced glutathione levels, as well as decreased levels of haptoglobin, a protein with antioxidant properties (2)(3)(4). In addition to an association with increased cardiovascular risk due to atherosclerosis, diabetes mellitus, obesity, and metabolic syndrome, oxidative stress is also associated with failed reproductive performance, including infertility, miscarriage, preeclampsia, and diabetes-related congenital malformations (5).…”
Section: Introductionmentioning
confidence: 99%